Rereading Jalāl al-Dīn al-Rūmī’s Wisdom Approach to Justice and Injustice - Ergin Ergül (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2021)
This paper discusses the wisdom approach to justice and injustice of Jalāl al-Dīn al-Rūmī, one of the greatest Sufi sages of all times. This famous Sufi master, in his background, was an eminent social thinker, intellectual, and especially a law scholar. Thus, it is not surprising that he dealt with these terms, which were critical concepts in past political thought in the West and the East, extensively in his works. Firstly, as a method, the study traces these two concepts in al-Rūmī’s works and mainly Masnavi. Then it connects them with their contemporary use. It is understood from al-Rūmī’s definitions of them, metaphors and stories accompanied by messages to judges and politicians, that he uses the concept of justice, especially in the sense of today’s rule of law and protection of human rights, and injustice in the sense of human rights violations and totalitarian policies. When we reread and rethink al-Rūmī’s mentioned concepts in this way, his political wisdom can inspire and guide both today’s Islamic world and humanity to overcome their challenges in these crucial areas.